Techniques for liver parenchymal transection: a meta-analysis of randomized controlled trials - Pamecha, Viniyendra (Blackwell Publishing Ltd, 2009)
BACKGROUND: Different techniques of liver parenchymal transection have been described, including the finger fracture, sharp dissection, clamp–crush methods and, more recently, the Cavitron ultrasonic surgical aspirator (CUSA), the hydrojet and the radiofrequency dissection sealer (RFDS). This review assesses the benefits and risks associated with the various techniques. METHODS: Randomized clinical trials were identified from the Cochrane Library Trials Register, MEDLINE, EMBASE, Science Citation Index Expanded and reference lists. Odds ratio (ORs), mean difference (MDs) and standardized mean differences (SMDs) were calculated with 95% confidence intervals based on intention-to-treat analysis or available-case analysis. RESULTS: We identified seven trials including a total of 556 patients. Blood transfusion requirements were lower with the clamp–crush technique than with the CUSA or hydrojet. The clamp–crush technique was quicker than the CUSA, hydrojet or RFDS. Infective complications and transection blood loss were greater with the RFDS than with the clamp–crush method. There was no significant difference between techniques in mortality, morbidity, liver dysfunction or intensive therapy unit and hospital stay. CONCLUSIONS: The clamp–crush technique is more rapid and is associated with lower rates of blood loss and otherwise similar outcomes when compared with other methods of parenchymal transection. It represents the reference standard against which new methods may be compared.